Bulk Crustal Properties and Layered Velocity Structure in Fujian, SE China: Constraints From P and S Receiver Functions - Goyal, Ayush; Hung, Shu-Huei (Frontiers in Earth Science, 2021)
Multiple tectonic events since the Neoproterozoic era have framed the present-day lithosphere in the Fujian province affiliated with the eastern part of the South China Block. Comprehensive information of the crustal structure and bulk properties can aid to understand the geological features and tectonic processes of still much debate in this region. An attempt is made in this study to explore crustal thickness and internal velocities across Fujian using the teleseismic receiver functions (RFs). The H-V stacking of joint P and S RFs improves to simultaneously estimate crustal thickness, average Vp and Vs, and derived Vp/Vs ratio and bulk sound speed in three backazimuth sectors for each of 17 stations. Furthermore, a Neighborhood Algorithm nonlinear inversion of P RFs is employed to determine the layered structures of Vs and Vp/Vs beneath all the stations. Results indicate the crustal thickness varies from at most ∼35 km in northwest Fujian to 30–35 km in the inland mountains and 27–30 km in the southeastern coasts. The inferred Moho geometry is nonplanar or inclined across the Zhenghe-Dapu (ZD) and Changle-Zhaoan (CZ) fault zones, especially in the southern ZD fault area. The average Vp/Vs suggests that the crust is predominantly felsic in the Wuyi-Yunkai orogen and intermediate-to-mafic in the Cretaceous magmatic and metamorphic zones. A high-velocity upper crust along the coastline is revealed, which attributes to the Pingtan-Dongshan metamorphic belt. At the sites near the ZD fault zone, the intracrustal negative discontinuity occurs at a shallower depth of ∼15 km marking an abrupt Vs decrease into the low-velocity mid-to-lower crustal layer, probably linked to the closed paleo-rift basin remnants. The lower crust across the Fujian is generally characterized by relatively lower Vs and higher Vp/Vs (1.80–1.84) consistent with those of the mafic-ultramafic rocks, which do not support the proposed extensive magmatic underplating in the Late Mesozoic.